Optimizing Pancasila Education Learning With PBL: Time Management Strategies To Build Students' Discipline And Independence - Namira Shifa Chaerunnisa; Yesa Angelina Maharani; Nilam Cahya Sholikah; Deni Zein Tarsidi (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
This research reveals that many students have low time discipline and independence. This often occurs because the learning methods used are less able to encourage students' personal involvement and the development of their skills (psychomotor).The implementation of Problem Based Learning (PBL) in Pancasila Education subjects can help students learn to better manage their time, thereby increasing their discipline and independence. Through PBL, important skills such as time management and responsibility can be taught, which are useful in everyday life. This article aims to explore time management strategies as an important factor in supporting the enhancement of student discipline and independence. It is hoped that problem based learning can optimize the PPKn learning process and significantly impact the students' character and social skills. The research method used in this study is qualitative research using a case study approach. The data collection techniques used in this case study research are observation, interview, and documentation methods. The results of the study show that PBL can help build student discipline and independence, although there are challenges in understanding the issues that affect their time management. This research recommends the use of reflective training and time management techniques, such as the Pomodoro technique, to support students in optimizing their skills in managing time and completing tasks.